Rapid Worsening of Symptoms and High Cell Proliferative Activity in Intra- and Extramedullary Spinal Hemangioblastoma: A Need for Earlier Surgery. (February 2017) - Imagama, Shiro; Ito, Zenya; Ando, Kei; Kobayashi, Kazuyoshi; Hida, Tetsuro; Ito, Kenyu; Ishikawa, Yoshimoto; Tsushima, Mikito; Matsumoto, Akiyuki; Nakashima, Hiroaki; Wakao, Norimitsu; Sakai, Yoshihito; et al.
Study Design: A retrospective analysis of a prospective database. Objective: To compare preoperative symptoms, ambulatory ability, intraoperative spinal cord monitoring, and pathologic cell proliferation activity between intramedullary only and intramedullary plus extramedullary hemangioblastomas, with the goal of determining the optimal timing for surgery. Methods: The subjects were 28 patients (intramedullary only in 23 cases [group I] and intramedullary plus extramedullary in 5 cases [group IE]) who underwent surgery for spinal hemangioblastoma. Preoperative symptoms, ambulatory ability on the McCormick scale, intraoperative spinal cord monitoring, and pathologic findings using Ki67 were compared between the groups. Results: In group IE, preoperative motor paralysis was significantly higher (100 versus 26%, p < 0.005), the mean period from initial symptoms to motor paralysis was significantly shorter (3.5 versus 11.9 months, p < 0.05), and intraoperative spinal cord monitoring aggravation was higher (65 versus 6%, p < 0.05). All 5 patients without total resection in group I underwent reoperation. Ki67 activity was higher in group IE (15% versus 1%, p < 0.05). Preoperative ambulatory ability was significantly poorer in group IE ( p < 0.05), but all cases in this group improved after surgery, and postoperative ambulatory ability did not differ significantly between the two groups. Conclusions: Intramedullary plus extramedullary spinal hemangioblastoma is characterized by rapid preoperative progression of symptoms over a short period, severe spinal cord damage including preoperative motor paralysis, and poor gait ability compared with an intramedullary tumor only. Earlier surgery with intraoperative spinal cord monitoring is recommended for total resection and good surgical outcome especially for an IE tumor compared with an intramedullary tumor.